Validation of the Infant Feeding Beliefs Questionnaire (IFBQ) among pregnant African- American women and their study partners. (1st October 2019) - Thompson, Amanda L.; Wasser, Heather; Bentley, Margaret E.
Abstract: Maternal feeding beliefs and practices have been associated with weight gain in infants and young children. Less work examines feeding beliefs prenatally or the feeding beliefs of other non-maternal caregivers (NMCs) who play important roles in infant feeding. This study validates a scale, the Infant Feeding Beliefs Questionnaire (IFBQ), to assess feeding beliefs during pregnancy among African-American women and other caregivers and tests whether the resulting belief constructs (laissez-faire, restrictive, responsive, pressuring and indulgent) are associated with maternal and NMC characteristics. Data come from 429 pregnant women and 374 NMCs including fathers, grandmothers and other family and friends enrolled in the baseline 28-week gestation visit of the Mothers and Others Study, a family-based, randomized control trial to support healthy infant feeding and prevent obesity. Confirmatory factor analysis (CFA) was used to test the fit of four a priori feeding constructs. Models were modified iteratively in mothers and then separately tested in the NMCs sample. Construct scores were created by averaging the remaining items and scale reliability was assessed. External validity was tested using bivariate and multivariable regression models. We validated five feeding belief constructs, measured through 8 sub-constructs. Reliability coefficients ranged from 0.58 for laissez faire to 0.76 for pressuring. Goodness of fit indices for CFA models indicated good fit with CFIs from 0.97 to 0.99 and RMSEA from 0.00 to 0.06. Construct scores differed significantly by depressive symptoms, obesity, education, income, and previous children in mothers and NMCs. The IFBQ may be used among mothers and NMCs to assess feeding beliefs beginning in the prenatal period, providing a tool to assess the longitudinal development of feeding beliefs and to highlight avenues for intervention on feeding practices during a critical period for behavior change.